An Argument for Salvage in Severe Lower Extremity Trauma with Posterior Tibial Nerve Injury: The Ganga Hospital Experience. Issue 6 (December 2015) - Momoh, Adeyiza O.; Kumaran, Senthil; Lyons, Daniel; Venkatramani, Hari; Ramkumar, Sanjai; Chung, Kevin C.; Sabapathy, S. Raja
Abstract : Background: Absence of plantar sensation is a critical factor considered in favor of amputation for patients with lower limb–threatening injuries. This study aims to assess outcomes of limb salvage in a group of patients with severe lower extremity injuries associated with posterior tibial nerve transection. Methods: The authors studied eight cases of limb salvage after traumatic injuries with documented tibial nerve laceration managed at Ganga Hospital, India. Functional and health-related quality-of-life outcomes were assessed. Outcomes from this case series were compared to outcomes of studies from a systematic literature review on salvage of the severely injured lower extremity. Results: Patients in this case series reported mild pain (median score, 20 on a visual analogue scale ranging from 0 to 100), with some return of plantar sensation in patients with tibial nerve repairs (median score, 2 of 5). Patients demonstrated a decrease in ankle motion (27.5 degrees' plantar flexion and 10 degrees' extension) and muscle strength (median heel flexor score, 3 of 5). All patients could ambulate independently. Quality of life and function measured by validated instruments revealed minimal disability. The authors identified 1767 articles on lower extremity trauma, and 14 articles were reviewed systematically. Relative to the case series, published articles reported similarly diminished ankle motion and muscle strength, with reports of mild pain in select studies. Patient-reported outcomes instruments found variations in the degree of physical disability based on the time from injury. Conclusion: Although limited in number, this case series demonstrates the value of limb salvage even for patients with posterior tibial nerve injury. Abstract : Supplemental Digital Content is available in the text.